Simulation training in non-cancer palliative care for healthcare workers: a systematic review of controlled studies. (14th August 2020) - Tropea, Joanne; Bicknell, Ross; Nestel, Debra; Brand, Caroline A; Johnson, Christina E; Paul, Sanjoy K; Le, Brian H; Lim, Wen Kwang
Abstract : Background: The need for healthcare workers (HCWs) to have skills and knowledge in non-cancer palliative care has been recognised. Simulation is increasingly being used for palliative care training, offering participants the opportunity to learn in a realistic environment and fully interactive way. Objective: The aim of this systematic review was to summarise and critically appraise controlled studies on simulation training in non-cancer palliative care for HCWs. Selection: Medline, CINAHL, PubMed and Cochrane Library databases were searched using palliative care and simulation terms. Randomised controlled trials (RCTs), non-randomised RCTs and controlled before-and-after (CBA) studies were included. Two reviewers independently screened titles and abstracts and undertook full article review using predefined selection criteria. Studies that met the inclusion criteria had data extracted and risk of bias assessed using the Cochrane Effective Practice and Organisation of Care risk of bias criteria. Findings: Five articles were included: three RCTs and two CBA studies. All studies assessed learners' palliative care communication skills, most studies evaluated learners' perception of change in skills and one study assessed impact on patient outcomes and learners' change in behaviour when applied in practice. There was variation in intervention content, intensity and duration, outcome measures and study design, making it difficult to compare and synthesise results. Conclusion: There is a paucity of evidence to support simulation training to improve non-cancer palliative care. This review highlights the need for more robust research, including multicentre studies that use standardised outcome measures to assess clinician skills, changes in clinical practice and patient-related outcomes.